A Research on the Comparative Effect of Active Dry Yeast and Inactivated-Stabilized Probiotic Yeast (Thepax) Added at Different Levels to Diets on Broiler Performance - Süleyman Çalışlar; Rahmi Kanat (Turkish Journal of Agriculture: Food Science and Technology)
This experiment was conducted to determine the effect of active yeast (AY) and inactive-stabilized yeast (Thepax) supplementation to the rations in different levels on broiler performance. In the experiment carried out according to the randomized plot design, there were 5 different treatment groups as control group (Group 1), 0.1% Thepax (Group 2), 0.2% Thepax (Group 3), 0.1% AY (Group 4) and 0.2% AY (Group 5). In the experiment, the effects of active and inactive yeasts on body weight gain (BWG), feed consumption, feed conversion rate, carcass weight (CW), carcass yield (CY), abdominal fat amount and mortality were investigated. In the present experiment, the final live weight, the cumulative feed consumption and feed conversion were insignificant. The statistical difference between the groups in the experiment was significant in carcass weight, but insignificant in the amount of abdominal fat and mortality rate. Inactive-stabilized yeast (Thepax 0.1%) was more effective than 0.2% AY on BWG. Only 0.1% Thepax increased the CW besides CY was high in 0.1%, 0.2% Thepax and 0.1% AY groups. It has been observed that active and inactive yeasts are used in broiler chickens without any problem.